Anticancer Activity Assessment and DNA Binding Properties of Two Binuclear Platinum (II) Complexes using Spectroscopic and Molecular Simulation Approaches - Alavianmehr, Mohammad M.; Ashrafi, Abolfazl; Yousefi, Reza; Haghighi, Mohsen G.; Abolmaali, Samira S.; Moosavi-Movahedi, Ali A.; Rad, Mohammad N.S. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Nowadays, the biological properties and anticancer activities of platinum-based drugs and metal coordination complexes have been receiving particular attention. These compounds have revealed clinical potential in cancer chemotherapy. Objective: In this research, two binuclear platinum complexes including [Pt2Cl2(bhq)2(μ-dppm)] (1) and [(p- MeC6H4)(bhq) Pt(μ-dppm)Pt(bhq)(CF3CO2)] (2) with bhq: benzo[h] quinolone and dppm: bis(diphenylphosphino) methane have been synthesized and evaluated for their anticancer activity against A2780 and A2780/RCIS cancer cell lines. Methods: The DNA binding and interaction of AMP/GMP nucleotide with these complexes were explored by several experimental and theoretical methods, including UV-Visible, fluorescence spectroscopic techniques and docking analysis. These complexes have demonstrated significant anticancer properties against cisplatinsensitive (A2780) and cisplatin-resistant (A2780/RCIS) human ovarian cancer cell lines. Results: The obtained results indicated that these complexes interact with DNA. Additionally, the fluorescence emission measurements indicated that the platinum complexes binding with DNA structure occurs through nonintercalative interaction. The molecular docking assessments have also revealed the binding of these platinum complexes through DNA grooves. Moreover, the results have indicated that complex 1 exhibited more anticancer activity than complex 2. Conclusion: The results of the DNA binding with these platinum complexes confirmed their potential antitumor properties. The substitution of -C6H4CH3 and -CO2CF3 groups in complex 2 with two chlorine atoms in complex 1 acquired the significant improvement of the anticancer activity against the cancer cell.
Keywords: platinum complex